2017
DOI: 10.1021/acssuschemeng.7b02657
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Halogen-Free Flame Retardant Cardanol Polyphosphazene Polybenzoxazine Networks

Abstract: We report on the preparation of hexa-functional cardanol (renewable phenolic compound) benzoxazine with a phosphazene core (C PN ) for use as a greener eco-friendly halogen-free flame retardant reactive additive for the formation of sustainable polyphosphazene polybenzoxazine networks for flame resistant applications. The structure and purity of the monomer was confirmed by Fourier transform infrared (FTIR), nuclear magnetic resonance ( 1 H-, 13 C-, 31 P NMR) and gel permeation chromatography studies. The C PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 52 publications
0
92
1
Order By: Relevance
“…Incorporation of 10 wt% C‐PN in C‐trisapm showed an increase in T g value from 100 to 120 °C which is attributed to the higher oxazine functionality of C‐PN assisting in the extension of cross‐link network formation during copolymerization. The copolymer composite revealed an improved thermal stability, LOI value, V‐0 rating with a simultaneous lowering in smoke density ratings supporting higher flame resistance characteristics …”
Section: Applications Of Cardanol Benzoxazinesmentioning
confidence: 83%
See 3 more Smart Citations
“…Incorporation of 10 wt% C‐PN in C‐trisapm showed an increase in T g value from 100 to 120 °C which is attributed to the higher oxazine functionality of C‐PN assisting in the extension of cross‐link network formation during copolymerization. The copolymer composite revealed an improved thermal stability, LOI value, V‐0 rating with a simultaneous lowering in smoke density ratings supporting higher flame resistance characteristics …”
Section: Applications Of Cardanol Benzoxazinesmentioning
confidence: 83%
“…The copolymer composite revealed an improved thermal stability, LOI value, V0 rating with a simul taneous lowering in smoke density ratings supporting higher flame resistance characteristics. [45] A sustainable onestep strategy toward lowtemperature cur able superparamagnetic composite based on smartly designed iron nanoparticles (IONPs) and Ctrisapm showed a pivotal role of capping agent in allowing their uniform dispersion in polymer (as supported by atomic force microscopy, Figure 9), with profound lowering of cure temperature (≈143 °C) of neat Ctrisapm. The studies also revealed the existence of oxidative polymerization along with conventional modes of ROP of the monomer.…”
Section: Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…[35] Recently, phosphazene nanotubes (PZS) filled epoxy and polybenzoxazine nanocomposites have been reported with significant improvements in flame retardation and mechanical properties as compared to the pristine polymers. [36][37][38][39] However, PZS has not been explored as a reinforcement for polyolefins, such as PP and polyethylene, to modify their properties.…”
mentioning
confidence: 99%